Pengaruh Struktur Corporate Governance Terhadap Initial Public Offering (Ipo)Underpricing Di Indonesia - ., Purwanto; Agustiningsih, Sri Wahyu; Insani, Salman Faris; Wahyono, Budi (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2015)
This research try to examine whether corporate governance when the company madean Initial Public Offering (IPO) affect the level of underpricing shares of companies that go public by using the period 2002-2012. This study focuses on the influence of corporate governance structure on the level of underpricing by using control variables underwriter reputation, return on assets (ROA), firm size, financial leverage, and return on equity (ROE). According to the results of previous studies, these variables generally tend to show a significant effect on underpricing in companies that go public. This research is ekspost facto (causal comparative). Sample selection method used was purposive sampling and sample used was 131 sample companies doing an Initial Public Offering on the Indonesia Stock Exchange in the period 2002-2012. This study uses regression testing models. Regression analysis showed that only the underwriter reputation significantly influence underpricin.